Definición en la enseñanza de geometría euclídea - GOTTE, Marcela; MANTICA, Ana María; MORIENA, Susana; RENZULLI, Fernanda; SCAGLIA, Sara (UNION MATEMATICA ARGENTINA, 2003)
Docentes de la FHUC de la U.N.L.